Understanding the systemic implications of climate transition risk: Applying a framework using Canadian financial system data - Gabriel Bruneau; Javier Ojea-Ferreiro; Andrew Plummer; Marie-Christine Tremblay; Aidan Witts (Bank of Canada, 2023)
Our study aims to gain insight on financial stability and climate transition risk. We develop a methodological framework that captures the direct effects of a stressful climate transition shock as well as the indirect - or systemic - implications of these direct effects. We apply this framework using data from the Canadian financial system. To capture the direct effects, we leverage the climate transition scenarios and financial risk assessment methods developed for the Bank of Canada and the Office of the Superintendent of Financial Institutions climate scenario analysis pilot project. We examine the direct effects - in the form of credit, market and liquidity risks - of the climate transition shock on financial system entities within the scope of our study. Specifically, we look at the public and private assets and derivatives portfolios of deposit-taking institutions, life insurance companies, pension funds and investment funds. To assess the indirect effects from the potential spread of the climate transition shock across an interconnected financial system, we extend an agent-based model to explore shock transmission channels such as cross-holding positions, business similarities, common exposures and fire sales. This model considers behavioural assumptions and rules, allowing us to understand the interconnectedness of the financial system. This work strengthens our understanding of how distinct entities within the financial system could be impacted by and respond to climate transition risks and opportunities, and of the potential channels through which those risks and opportunities may spread. More generally, this work contributes to building standardized systemic risk assessment and monitoring tools.
Keywords: Q54; C63; G01; G10; G20; 330; Climate change; Financial stability; Financial institutions; Financial markets; Economic models